Ship propulsion in waves by actively controlled flapping foils. (August 2015) - Belibassakis, K.A.; Filippas, E.S.
Highlights: Hydrodynamic performance of flapping-foil thrusters operating in random waves. Significant thrust production by the examined biomimetic system. Investigation of the effects of finite foil submergence and finite water depth. Enhancement of dynamic stabilisation and reduction of added wave resistance. Abstract: Flapping wings located beneath or to the side of the hull of the ship are investigated as unsteady thrusters, augmenting ship propulsion in waves. The main arrangement consists of horizontal wing(s) in vertical oscillatory motion which is induced by ship heave and pitch, while rotation about the wing pivot axis is actively controlled. In this work we investigate the energy extraction by the system operating in irregular wave conditions and its performance concerning direct conversion to propulsive thrust. More specifically, we consider operation of the flapping foil in waves characterised by a spectrum, corresponding to specific sea state, taking into account the coupling between the hull and the flapping foil dynamics. The effect of the wavy free surface is accounted for through the satisfaction of the corresponding boundary conditions and the consideration of the wave velocity on the formation of the incident flow. Numerical results concerning thrust and power coefficients are presented, indicating that significant thrust can be produced under general operating conditions. The present work can be exploited for the design and optimum control of such systems extracting energy from sea waves for augmenting marine propulsion in rough seas, with simultaneous reduction of ship responses offering also dynamic stabilisation.